EXPLORING THE LIMITS OF THE TECHNOLOGY S‐CURVE. PART I: COMPONENT TECHNOLOGIES - CHRISTENSEN, CLAYTON M. (Production and Operations Management, 1992)
The technology S‐curve is a useful framework describing the substitution of new for old technologies at the industry level. In this paper I use information from the technological history of the disk drive industry to examine the usefulness of the S‐curve framework for managers at the firm level in planning for new technology development. Because improvements in over‐all disk drive product performance result from the interaction of improved component technologies and new architectural technologies, each of these must be monitored and managed. This paper focuses on component technology S‐curves, and a subsequent paper, also published in this issue of the journal, examines architectural technology Scurves. Improvement in individual components followed S‐curve patterns, but I show that the flattening of S‐curves is a firm‐specific, rather than uniform industry phenomenon. Lack of progress in conventional technologies may be the result, rather than the stimulus, of a forecast that the conventional technology is maturing, and some firms demonstrated the ability to wring far greater levels of performance from existing component technologies than other firms. Attacking entrant firms evidenced a distinct disadvantage versus incumbent firms in developing and using new component technologies. Firms pursuing aggressive Scurve switching strategies in component technology development gained no strategic advantage over firms whose strategies focused on extending the life of established component technologies.